2016
DOI: 10.1042/cs20160108
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and the brain: neural control of cardiovascular changes during pregnancy and neurological outcomes of preeclampsia

Abstract: Preeclampsia (PE) is a form of gestational hypertension that complicates ~ 5 percent of pregnancies worldwide. Over 70 percent of the fatal cases of PE are attributed to cerebral edema, intracranial hemorrhage, and eclampsia. The etiology of PE originates from abnormal remodeling of the maternal spiral arteries, creating an ischemic placenta that releases factors that drive the pathophysiology. An initial neurological outcome of PE is the absence of the autonomically regulated cardiovascular adaptations to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 248 publications
(342 reference statements)
2
37
0
5
Order By: Relevance
“…Besides, lysine catabolism is related to biosynthesis of homoarginine which is elevated in normal pregnancy [13], with some studies linking its elevation to pregnancy disorders, including preeclampsia [55]. Physiological manifestations of pre-eclampsia and eclampsia, associated with nearly one-tenth of all maternal deaths [56], involve changed cerebral hemodynamics and hypertensive encephalopathy [57][58][59], potentially linked to impaired signaling by homoarginine, known as a predictor of cardiovascular risk and mortality [3]. Alternatively, homoarginine is synthesized from arginine and glycine.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, lysine catabolism is related to biosynthesis of homoarginine which is elevated in normal pregnancy [13], with some studies linking its elevation to pregnancy disorders, including preeclampsia [55]. Physiological manifestations of pre-eclampsia and eclampsia, associated with nearly one-tenth of all maternal deaths [56], involve changed cerebral hemodynamics and hypertensive encephalopathy [57][58][59], potentially linked to impaired signaling by homoarginine, known as a predictor of cardiovascular risk and mortality [3]. Alternatively, homoarginine is synthesized from arginine and glycine.…”
Section: Discussionmentioning
confidence: 99%
“…; Hammer and Cipolla ; von Dadelszen and Magee ; Logue et al. ). Complications of PE appear to be more diverse than other hypertensive disorders of pregnancy with dysfunction in organ systems like the heart, kidney, liver, brain, and placenta (Shen et al.…”
Section: Introductionmentioning
confidence: 99%
“…PE is clinically defined as new-onset hypertension occurring during the second half of pregnancy along with additional systemic vascular abnormalities in the mother. These include reduced cardiac reserve, cerebral vascular autoregulation, and renal hemodynamics along with increased glomerular injury, pulmonary edema, and cerebral edema (Stillman and Karumanchi 2007; American College of Obstetricians , Gynecologists, and Task Force on Hypertension in Pregnancy, 2013; Gandhi et al 2014;Melchiorre et al 2014;Hammer and Cipolla 2015;von Dadelszen and Magee 2016;Logue et al 2016). Complications of PE appear to be more diverse than other hypertensive disorders of pregnancy with dysfunction in organ systems like the heart, kidney, liver, brain, and placenta (Shen et al 2017;Tooher et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The global incidence rate is 4.6% of pregnancies (Abalos et al, 2013), leading to 60,000 maternal deaths per year (Logue et al, 2016). The grave consequences of PE on maternal health are mainly attributed to cerebral edema, intracranial hemorrhage and eclampsia Zeeman, 2009), which some studies have suggested to be caused by abnormal functions of the autonomic nervous system mediated by placenta-derived factors (Eneroth-Grimfors et al, 1994;Melchiorre et al, 2014;Voss et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The global incidence rate is 4.6% of pregnancies, 4 leading to 60,000 maternal deaths per year. 5 The grave consequences of PE on maternal health are mainly attributed to cerebral edema, intracranial hemorrhage and eclampsia, 6,7 which some studies have suggested to be caused by abnormal functions of the autonomic nervous system mediated by placenta-derived factors. [8][9][10] PE has significant consequences on fetal development and growth, often leading to perinatal and infant morbidity or mortality 1 and contributes preterm births 11 and ~15% cases of fetal growth restriction (FGR).…”
Section: Introductionmentioning
confidence: 99%